A New Face of Tourism: Understanding Travel Experiences of New Zealand Inbound Generation Z - Robinson, Victor Mueke (Auckland University of Technology, 2019)
Any successful tourism industry player requires not only the ability to recognize change, but to also effectively respond to this change. Generational change is one such occurrence, offering both opportunities and challenges for tourism destinations. Significant studies on generation cohorts have been conducted over the years. However, each new generation is confronted by unique contemporary circumstances providing avenues for delineated and context-based perspectives. A new generation (Generation Z) is entering adulthood, necessitating specific research. Extant literature reveals a proliferation of market surveys but a paucity of academic research on this generation. Moreover, studies have tended to focus on Europe and the USA creating a gap in literature within New Zealand. Accordingly, this study aims to contribute towards plugging these identified gaps. The aim of the study is to understand the travel experiences of New Zealand inbound Generation Z travelers whilst highlighting the emergence of this new generation. This is a qualitative study involving the Constructivist Grounded Theory Methodology. The approach taken allowed for a deep interrogation of the data which was gathered through 12 semi-structured interviews and data mining from five travel blogs. From the analysis process, six core categories emerged. These core categories are travel patterns, destination profile, context, reasons for travel, identity, and realm of experience. While some of the findings and categories fit within the extant discourse on the notion of experience, two core categories are unique to this research – context and realm of experience. Findings further indicate that, New Zealand inbound Generation Z had similar travel patterns. Their image of New Zealand is predominantly centred on the beautiful landscape and the residents’ culture. The key outcome of this study was a new theoretical framework of Generation Z travel experiences in New Zealand. The framework proposes experience as being realized in either physiological realm, psychological realm or spiritual realm. The realms constitute the totality of a human being. These realms (experiences) are influenced by three different factors - immediate influences, destination influences and global influences; all through multiple interfaces. It is the gestalt of these aspects that constitutes an understanding of Generation Z travel experiences. Observably, the theoretical framework shifts the focus from destination to the tourist/traveler. This is in keeping with a similar trend by Tourism New Zealand of laying more emphasis on the people rather than the landscape.
Keywords: Generation Z; Realm of experience; Context; Global; Social media; Influence; Interfaces